FORMULATION AND EVALUATION OF HERBAL MOISTURIZING CREAM. - Kadam Prity Kacharu; Pawar Mahesh Sopan; Dhotre Sahil Sanjay; Londhe Sayali Shivaji; Pawar Pratiksha Babusha; Garud Neha Sunil; Dr. Veer Sujata Umakant; Dr. Kopnar Vishal Pandit; Dr. Khedkar Amol Navnath (The Bioscan, 2026)
The main objective is to formulate and evaluate moisturizing cream. Firstly, fresh part of plant collected after that extraction done so that proper formulation should be done. The importance of herbs in the cosmeceutical has been extensively increased in personal care system and there is a great demand for herbal cosmetics now days. Herbal cosmetics are a non-toxic, safe, effective formulation which improves patient compliance by the Utilization of herbal extracts and hence it would be highly acceptable then synthetic ones. The formulated cream has good results on spread ability, wash-ability, pH, irritancy and has good therapeutic effects. There is also no phase separation during observation of moisturizing cream. This prepared moisturizing cream is safe for use and it is developed from herbal products. Herbal cosmetics are widely accepted in a belief that it is safe for use and has no side effect. All the chemicals used in formulation makes the cream very stubble and helps in making good cream.